PERBANDINGAN HASIL BELAJAR DAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATERI REAKSI REDOKS KELAS X MA AL-FATAH AMBON SEBELUM DAN SELAMA MASA PANDEMI COVID-19 - Napsin Palisoa (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2021)
This study aims to determine the differences in learning outcomes and students' learning motivation on redox reaction material for class X IPA MA Al-Fatah Ambon before and during the covid-19 pandemic. The sample in this study consisted of 22 students who studied redox reaction material in class X offline and 22 students who studied redox reactions online. This study uses a quantitative experimental research method with a comparative study research design. Collecting data in this study using a questionnaire, documentation and observation. Questionnaires were used to measure students' learning motivation, documentation was used to measure learning outcomes (cognitive, affective, and psychomotor) of students in class X before the pandemic and cognitive learning outcomes in class X during the pandemic, while observation was used to measure affective and psychomotor learning outcomes. Class X students during the COVID-19 pandemic. The documentation used is the value of students in the redox reaction material for the even semester 2019/2020 and even semester 2020/2021, then observations are made by participating in live online learning. The data obtained were then analyzed using descriptive and inferential data analysis methods. Based on the results of descriptive data analysis of learning motivation and student learning outcomes on redox reaction material for class X before and during the pandemic period, it was in the moderate category, while based on the results of inferential data analysis using Mann-Whitney analysis for learning motivation, the Asymp sig value was obtained. (2-tailed) 0.646 and 0.000 learning outcomes. The results show that there are no differences in students' learning motivation before and during the COVID-19 pandemic, so H0 is accepted, and there are differences in student learning outcomes before and during the COVID-19 pandemic, so H0 is rejected.